Sexual Cultures - Weeks, Jeffrey. author. aut Link
XII, 317 p.
Keywords: The new sociology of sexuality has a two-fold aim: to demonstrate how the social shapes the sexual; and to analyse how the sexual in turn becomes a focal point for personal identity, cultural anxiety value debates and political action. Drawing on papers from the 1994 British Sociological Association annual conference on 'Sexualities in Social Context', this volume brings together key contributors to this stimulating new approach. Topics covered include theoretical developments, the relationship between history and contemporary controversies, community and identity, especially in the context of AIDS, value conflicts and changes in the meanings of intimacy. The book as a whole offers a significant intervention into debates on sexuality, and a thoughtful contribution to the broadening of the sociological agenda.